2008
DOI: 10.1183/09031936.00176807
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in lung injury and fibrosis

Abstract: Pulmonary fibrosis is characterised by fibroblast accumulation and alveolar epithelium denudation. Increased apoptosis of alveolar epithelial cells and decreased apoptosis of fibroblasts may play an important role in the pathogenesis of disease. Inflammatory cells can modulate apoptosis of other cell types, both by removal of apoptotic debris and by cytokine production, thus preserving a pro-fibrotic environment. In the present review, some of the mechanisms by which apoptosis may contribute to the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 86 publications
2
96
0
9
Order By: Relevance
“…Apoptotic cells undergo various cellular morphological changes, including cell shrinkage, chromatin condensation, membrane blebbing, oligonucleosomal DNA cleavage and translocation of phosphatidylserine (PS) from the inner to the outer leaflet of the plasma membrane and activation of a family of cysteine proteases called caspases (Elmore, 2007;Drakopanagiotakis et al, 2008). Typical apoptotic signaling pathway includes extrinsic (death receptor) and intrinsic (mitochondrial) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic cells undergo various cellular morphological changes, including cell shrinkage, chromatin condensation, membrane blebbing, oligonucleosomal DNA cleavage and translocation of phosphatidylserine (PS) from the inner to the outer leaflet of the plasma membrane and activation of a family of cysteine proteases called caspases (Elmore, 2007;Drakopanagiotakis et al, 2008). Typical apoptotic signaling pathway includes extrinsic (death receptor) and intrinsic (mitochondrial) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The alteration in lung function and the presence of tumor cells remaining may be the cause of the lack of relationship with the survival obtained in mice. [33][34][35][36] It may be important to develop cell-specific antiapoptotic strategies, rather than strategies aimed at blocking apoptosis of types of cells within the lungs. Other studies have reported similar survival profiles for pulmonary …”
Section: Tunel Assaymentioning
confidence: 99%
“…Epithelial cell death is a crucial early step in the development of the disease (18), followed only later by the fibrotic stage. IPF is triggered by alveolar basement membrane disruption and, in the presence of persisting injurious pathways (19), activated TGF-β leads to enhanced epithelial apoptosis and epithelial-to-mesenchymal transition as well as fibroblast (20,21) transformation into myofibroblasts which are resistant to apoptosis (22,23). In the present study, alveolar epithelial cell apoptosis was measured using MTT assay.…”
mentioning
confidence: 99%